2018
DOI: 10.1097/mpg.0000000000001745
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Gluten‐free Diet on Clinical Symptoms and the Intestinal Mucosa of Patients With Potential Celiac Disease

Abstract: In this prospective study, we evaluated the effect of gluten-free diet (GFD) in a cohort of 65 children with potential celiac disease. Patients received GFD for signs/symptoms (N = 47) or parents' choice (N = 18). Most frequent signs/symptoms were low body mass index (36%), recurrent abdominal pain (34%), and diarrhea (19%). Of the 35/47 patients followed-up on GFD, only 54% (19/35) showed a complete clinical response. In 9 of 65 patients an intestinal biopsy was also performed after at least 1 year of GFD. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
18
0
Order By: Relevance
“…In another study, Mandile et al, evaluated the effect of GFD on clinical symptoms and mucosal histology in children with potential CD [ 58 ]. After one year on GFD no significant differences were observed in terms of Marsh grade, lamina propria CD25+ cells, CD3+ and γδ+ intraepithelial lymphocytes density and intestinal anti-TG2 deposits.…”
Section: Gluten-free Diet In Potential Celiac Diseasementioning
confidence: 99%
“…In another study, Mandile et al, evaluated the effect of GFD on clinical symptoms and mucosal histology in children with potential CD [ 58 ]. After one year on GFD no significant differences were observed in terms of Marsh grade, lamina propria CD25+ cells, CD3+ and γδ+ intraepithelial lymphocytes density and intestinal anti-TG2 deposits.…”
Section: Gluten-free Diet In Potential Celiac Diseasementioning
confidence: 99%
“…The study cohort included either genetically at-risk children diagnosed by screening early in life or older children tested for CD for other reasons. A recent study evaluating the effect of GFD in a cohort of 65 symptomatic children with potential CD showed that symptoms after GFD improve in only about half of the cases [13]. Therefore, the authors suggested caution before starting a GFD in this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Potential CD is used to describe patients with normal small intestinal mucosa who are at increased risk for development of CD as indicated by positive CD serologic findings. 21,22 Celiac disease autoimmunity is characterized by increased TTG antibody or endomysial antibody (EMA) on at least 2 occasions when the status of the duodenal histology is unknown. This feature could be the clinical presentation of potential CD (if the biopsy result is negative), vs actual CD (if the biopsy result is positive).…”
Section: Cd-related Definitionsmentioning
confidence: 99%